Model Manajemen Organisasi Kedaerahan dalam Membangun Kesadaran Kolektif Berbasis Kearifan Lokal - Febi Febrianto (CV Narasi Khatulistiwa Indonesia, 2025)
This study aims to formulate a model of regional student organization management based on local wisdom at Nurul Jadid Islamic Boarding School, Probolinggo. The research focuses on how the values of struggle taught by KH. Zaini Mun’im—embodied in the Trilogy and Five Student Awareness—are internalized within the management system of student organizations to build collective awareness and social character. This study employs a qualitative approach with a case study design, involving members of the Santri Communication Forum (FKS), Orsat, and Orda as key subjects. Data were collected through in-depth interviews, participant observation, and document analysis, and then analyzed using Miles and Huberman’s interactive model. The findings reveal that the management of student organizations at Nurul Jadid integrates modern managerial systems with pesantren (Islamic boarding school) values. Each stage of management—planning, organizing, implementation, and evaluation—is carried out based on principles of struggle, deliberation, sincerity, and social responsibility. These values serve not only as moral guidelines but also as the driving energy of the organizational culture. The resulting model is holistic and transformative, fostering students’ collective awareness as agents of social change and guardians of humanitarian values. This study contributes theoretically to the development of value-based management models in the context of Islamic boarding school education